Usuń nawiasy i wykonaj redukcję wyrazów podobnych.

a) (a+b) + (2a-b)
b) 2x + (3y-2z) + (3z-2x)
c) -5ab + (bc-2ab) + 4cb
d) (5xy -2xz) + (3zx-7zyx)
e) (m + n) - (2m+3n)
f) (2xy + 4y2) - (3yx - 2y2małe)
g) 3abc - (2cab + 5bac)
h) 10x2y - (5xy2 - 8x2y)
proszę o szybkie rozwiązanie;)

1

Odpowiedzi

2010-02-22T18:04:05+01:00
A) (a+b) + (2a-b) = a + b + 2a - b = 3a [ b zredukowało się z - b]
b) 2x + (3y-2z) + (3z-2x) = 2x + 3y - 2z + 3z - 2x = 3yz[2x zredukowało się z -2x]
c) -5ab + (bc-2ab) + 4cb = -5ab + bc - 2ab + 4cb = 7ab + bc + 4cb
d) (5xy -2xz) + (3zx-7zyx) = 5xy - 2xz + 3zx - 7 zyx =
e) (m + n) - (2m+3n) = m + n - 2m + 3n = m4n